Learning in friendship groups: developing students’ conceptual understanding through social interaction - Senior, Carl; Howard, Chris (Frontiers in Psychology, 2014)
The role that student friendship groups play in learning was investigated here. Employing a critical realist design, two focus groups on undergraduates were conducted to explore their experience of studying. Data from the ‘case-by-case’ analysis suggested student-to-student friendships produced social contexts which facilitated conceptual understanding through discussion, explanation and application to ‘real life’ contemporary issues. However, the students did not conceive this as a learning experience or suggest the function of their friendships involved learning. These data therefore challenge the perspective that student groups in higher education are formed and regulated for the primary function of learning. Given these findings, further research is needed to assess the role student friendships play in developing disciplinary conceptual understanding.